2012
DOI: 10.18388/abp.2012_2153
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of bilirubin ditaurate by the intestinal bacterium Clostridium perfringens.

Abstract: Bilirubin is degraded in the human gut by microflora into urobilinoids. In our study we investigated whether the bilirubin-reducing strain of Clostridium perfringens can reduce bilirubin ditaurate (BDT), a bile pigment of some lower vertebrates, without hydrolysis of the taurine moiety. C. perfringes was incubated under anaerobic conditions with BDT; reduction products were quantified by spectrophotometry and separated by TLC. Based on Rf values of BDT reduction products and synthetic urobilinogen ditaurate, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…The broad specificity of anaerobic bacterial enzymes found in the human gastrointestinal tract for bile pigments has been previously demonstrated 13 and it has been suggested that bilirubin reducing enzymes serve for the disposal of electrons produced by fermentolytic processes performed by these bacteria, however, the mechanisms of biliverdin/bilirubin metabolism are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The broad specificity of anaerobic bacterial enzymes found in the human gastrointestinal tract for bile pigments has been previously demonstrated 13 and it has been suggested that bilirubin reducing enzymes serve for the disposal of electrons produced by fermentolytic processes performed by these bacteria, however, the mechanisms of biliverdin/bilirubin metabolism are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota then converts it to stercobilin for excretion in stool (4). The absence of gut microflora required for the conversion of bilirubin to stercobilin, such as Clostridium ramosum, Clostridium perfringens, Clostridium difficile, and Bacteroides fragilis, results in higher bilirubin levels in the intestinal tract, which then leads to elevated enterohepatic circulation (5).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal bacterial species, including Bacteroides fragilis, Clostridium ramosum, Clostridium perfringens, and Clostridium difficile, have been shown to catabolize bilirubin to urobilinogen [29][30][31][32] , although we could not assign these bacterial species in our results (Fig. 1C).…”
Section: Discussionmentioning
confidence: 77%